Effect of the upper limbs muscles activity on the mechanical energy gain in pole vaulting - Frere, J.; Göpfert, B.; Slawinski, J.; Tourny-Chollet, C. (Journal of Electromyography and Kinesiology, 2012)
The shoulder muscles are highly solicited in pole vaulting and may afford energy gain. The objective of this study was to determine the bilateral muscle activity of the upper-limbs to explain the actions performed by the vaulter to bend the pole and store elastic energy. Seven experienced athletes performed 5-10 vaults which were recorded using two video cameras (50 Hz). The mechanical energy of the centre of gravity (CG) was computed, while surface electromyographic (EMG) profiles were recorded from 5 muscles bilateral: deltoideus, infraspinatus, biceps brachii, triceps, and latissimus dorsi muscles. The level of intensity from EMG profile was retained in four sub phases between take-off (TO1) and complete pole straightening (PS). The athletes had a mean mechanical energy gain of 22% throughout the pole vault, while the intensities of deltoideus, biceps brachii, and latissimus dorsi muscles were sub phases-dependent (p < 0.05). Stabilizing the glenohumeral joint (increase of deltoideus and biceps brachii activity) and applying a pole bending torque (increase of latissimus dorsi activity) required specific muscle activation. The gain in mechanical energy of the vaulter could be linked to an increase in muscle activation, especially from latissimus dorsi muscles.